Interface and strain effects on the fabrication of suspended CVD graphene devices. (June 2015) - Aydin, O.I.; Hallam, T.; Thomassin, J.L.; Mouis, M.; Duesberg, G.S.
Abstract: It is known that the fabrication of graphene NEMS raises several technological issues. The most mentioned among these is beam collapse due to the capillary effects. However, we found that controlling the quality of the interface of graphene and the etch mask requires at least equal attention. By taking this into account, we succeeded developing a robust route for the fabrication of suspended graphene structures, using technological steps compatible with large-scale fabrication. AFM and Raman characterization results are used to probe suspension, added defects and strain evolution during the process.